Systemic arterial hypertension: clinical and assistential aspects - Lucena, Amália de Fátima (2008)
This article is a literature review about the concepts of systemic arterial hypertension, it`s incidence, the diagnostic methods and used treatments. It emphasizing the nurse`s role in the patients care, based on the authors` nursing practice at Hospital de Clínicas Porto Alegre. The authors describe measures to prevent and promote health, as well as advanced actions during hypertension crisis and emergency cases.